Characterization of ecologically dysfunctional municipalities: a contribution to Environmental Democracy - Oliveira, Celso Maran de (Revista Nacional de Gerenciamento de Cidades, 2021)
This research aims to promote a discussion on how to characterize an ecologically dysfunctional municipality, in terms directly linked to environmental legal noncompliance, and how it can impact the axes of Environmental Democracy, based on the identification of institutionalized environmental conflicts by governmental agencies that have a duty to conduct investigations and punish its offenders. The methodology used was a documental analysis of works published on the subject in books, specialized magazines, scientific articles available in libraries or on the internet; and the analysis of a case study, which took place in a medium-sized municipality in the state of São Paulo. Using the methodology, we were able to characterize ecologically dysfunctional municipalities, and their impacts on the structural axes of Environmental Democracy, in order to provide access to information, increase citizen participation, and resolve environmental conflicts.